" (Disability, inclusion and public employment, is it possible to improve their relationship? Reflections from a pilot experience at the University of Zaragoza - Mira-Aladrén, Marta; Yagüe-Sanjuán, Natalia; Latorre-Dena, Fernando (Acciones e Investigaciones Sociales, 2024)
Introduction: Legislation on public employment and the rights of people with disabilities recognises an obligation to reserve 2% of the places advertised for people with intellectual disabilities. Despite this, the idiosyncrasies of public administrations in Spain and, in particular, of universities, make it difficult for these rights to be effective. Therefore, a pilot programme of theoretical and practical training and promotion of empowerment is proposed in order to promote their inclusion in the labour market. Objective: The aim of this article is to present and evaluate this pilot programme, putting forward proposals to improve access to public employment for this group. Methodology: For this purpose, its effectiveness was evaluated, using the Quality-of-Life Scale, as well as the satisfaction of families, participants and professionals with it, via an ad hoc questionnaire. Results: The results show that, despite the improvement in quality of life, deficits were detected, such as the need for awareness and training for the university community, the relevance of labour mediation and the importance of carrying out individualised adaptations. Discussion: A series of improvements in the implementation of programmes of this type, as well as in the inclusion of people with intellectual disabilities in public employment, in general, are proposed.